Canting Expedition: Herpetofauna Diversity in the Mendolo Village, Lebakbarang, Pekalongan - Gunawan, Dwi Ariya; Wijayati, Qadriyah Fitri Catur; Rahmajati, Raden Roro Digwikan; Fitriana, Isnaini; Fatmawati, Dwi; Arif , Irvanda Mustofa (Universitas Atma Jaya Yogyakarta, 2024)
Central Java is an area that has natural forests with quite high biodiversity potential, one of which is Mendolo Village, Lebakbarang, Pekalongan. The diversity of herpetofauna species is one of its potential biodiversity. Data collection on herpetofauna in Mendolo Village has not yet been carried out, even though this village is in direct contact with natural forests with great potential. The aim of this research is to reveal the diversity of herpetofauna types at this location. The method used is VES (Visual Encounter Survey). The data obtained was then analyzed using the Shannon-Wiener Diversity Index. There were 23 species of reptiles and 16 species of amphibians, with a Diversity Index value of 2.942 for reptile types and 2.28 for amphibians. The conclusion that can be drawn is that the diversity of herpetofauna species in Mendolo Village is in the quite high category.